The Development and Enlightenment of Good Cadre Standards. Issue 5 (March 2019) - Han, Wang; Bo, Peng
Abstract: The enterprise supplementary pension insurance is an additional insurance specially established for the employees of the enterprise after the basic pension insurance formulated by the enterprise in accordance with its own economic strength and after fulfilling the obligation to pay the basic old-age insurance premium. The enterprise supplementary pension insurance is at the second level in China's multi-level endowment insurance system, which is the supplement and improvement of the enterprise's basic endowment insurance for the enterprise employees. However, the development of supplementary pension insurance for Chinese enterprises has been slow, and the government's policy is undoubtedly an important reason. This paper attempts to explore the policy status of China's enterprises supplementing pension insurance, analyze the policy factors that restrict its development, and propose the basic ideas and policy recommendations for strengthening the supplementary pension system of Chinese enterprises.